Muscular-skeletal diseases require scientifically designed sewing workstations - Polajnar, Andrej (Strojniški vestnik, 2010)
The paper describes the adjustment of the sewing workstation with respect to working postures and workers' perceptions based on the results of a survey research carried out in 32 sewing workstations in different garment production factories in Slovenia. Poor posture of the trunk, neck and upper extremities, and the monotonous repetitive movements result in a high prevalence of musculoskeletal complaints affecting back, neck and upper extremities among sewing machine operators. Several studies have confirmed that working postures are still a common problem in garment industry and ergonomically designed workstations can considerably reduce the above-mentioned problems. Therefore, the main purpose of the paper is to formulate all ergonomic recommendations for the modification of sewing machineworkstations.
Keywords: delovna mesta; ergonomija; mišično-skeletne bolezni; šivilje